Assessment of genetically modified maize MON 95379 for food and feed uses, under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐NL‐2020‐170). (15th November 2022) - ,; Mullins, Ewen; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Naegeli, Hanspeter; Nogué, Fabien; et al.
Abstract: Genetically modified maize MON 95379 was developed to confer insect protection against certain lepidopteran species. These properties were achieved by introducing the cry1B.868 and cry1Da_7 expression cassettes. The molecular characterisation data and bioinformatic analyses do not identify issues requiring food/feed safety assessment. None of the identified differences in the agronomic/phenotypic and compositional characteristics tested between maize MON 95379 and its conventional counterpart needs further assessment. The GMO Panel does not identify safety concerns regarding the toxicity and allergenicity of the Cry1B.868 and Cry1Da_7 proteins as expressed in maize MON 95379. The GMO Panel finds no evidence that the genetic modification impacts the overall safety of maize MON 95379. In the context of this application, the consumption of food and feed from maize MON 95379 does not represent a nutritional concern in humans and animals. Therefore, no post‐market monitoring of food/feed is considered necessary. In the case of accidental release of viable maize MON 95379 grains into the environment, this would not raise environmental safety concerns. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of maize MON 95379. The GMO Panel concludes that maize MON 95379 is as safe as its conventional counterpart and the tested non‐GM maize varieties with respect to potential effects on human and animal health and the environment.